The Impact of Commitment Savings Accounts : The Case of Malawi - Gine, Xavier (World Bank, Washington, DC, 2012)
In order to understand the impact of facilitating access to savings accounts and to examine the importance of these barriers for formal savings, author designed a field experiment among smallholder cash crop farmers in Malawi. In partnership with a local microfinance institution, author randomized offers of account-opening and deposit assistance for formal savings accounts. In order to test the importance of individual self-control problems or pressure to share resources with others in the social network, treated farmers were randomly assigned to one of two types of savings interventions. The first group was offered an 'ordinary' bank account with standard features. The second group was offered the ordinary account as well as a 'commitment' savings account.